2000
DOI: 10.1046/j.1468-3083.2000.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive and deep dermatophytosis caused by Trichophyton mentagrophytes var. Interdigitalis in an HIV‐1 positive patient

Abstract: This is the first reported case of deep dermatophytosis caused by T. mentagrophytes in an HIV-positive patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 7 publications
2
22
0
1
Order By: Relevance
“…We found 4 extensive lesions, and 1 case involved the gluteal region, groin, and thighs. Regarding the number of cutaneous lesions in each patient, 3 presented with 6 or more lesions, in agreement with reports of such occurrence of numerous lesions of tinea in these patients (Porro et al, 1997;Muñoz-Pèrez et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found 4 extensive lesions, and 1 case involved the gluteal region, groin, and thighs. Regarding the number of cutaneous lesions in each patient, 3 presented with 6 or more lesions, in agreement with reports of such occurrence of numerous lesions of tinea in these patients (Porro et al, 1997;Muñoz-Pèrez et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Less common etiologic agents of tinea in humans have been described as promoting atypical presentations, especially in association with severe immunosuppression. Among these agents, species of the genus Microsporum have been isolated (Bournerias et al, 1996;King et al, 1996;Porro et al, 1997;Muñoz-Pèrez et al, 2000;Galhardo et al, 2005;Nenoff et al, 2007;Narang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Trichophyton rubrum identified on the lesions of our patient is the dermatophytosis mostly the one founded in our country on persons infected by HIV according to Zida and al [10]. It is also one of the pathogenic agent most frequently met on this type of patient [1,5,11]. The profuse seborrheic dermatitis was raised in front of the macular high pigmented aspect of the lesions, the topography on the face (mainly the arcades and the ciliary edge) and the front temporal area of the hair.…”
Section: Discussionmentioning
confidence: 63%
“…Widespread and atypical dermatophyte infections may occur only rarely in patients with immunosuppression due to systemic steroids, chemotherapy (1), Cushing's syndrome (2), renal transplantion (3), or AIDS (4–9). In HIV‐infected patients, atypical extensive scaly erythematous lesions (4–6), that looked like seborrheic dermatitis, psoriasis, Norway scabiei, or dermatophyte granulomas (79), have been reported. Crosby et al (7) reported a dermatophytosis mimicking Kaposi's sarcoma in HIV positive patients.…”
Section: Introductionmentioning
confidence: 99%